(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
We are interested now by the situations on estimation that appear in cartoon series in which mathematics is an essential part of the storyline. We analyse in detail one of them, taken from the first season of Cyberchase, observing how the characters not only put into play different techniques and strategies to solve problems, but they learn with each one of them. In addition, an evolution in the attitudes and beliefs of some of the protagonists towards the mathematical activity is detected. This analysis also reveals some mistakes or inaccuracies in the dubbing process, which would be avoidable if, as in the original production, there were experts in the field of mathematics education. We complete the article mentioning other cartoon series involving estimation situations.